Targeting bone tumours with 45S5 bioactive glass - Fellenberg, Jörg; Losch, Sarina; Arango-Ospina, Marcela; Hildenbrand, Nina Marie; Tripel, Elena; Deng, Lingyun; Renkawitz, Tobias; Westhauser, Fabian; Lehner, Burkhard; Boccaccini, Aldo R. (International journal of molecular sciences, 2024)
Despite advances in treatment modalities, bone tumour therapies still face significant challenges. Severe side effects of conventional approaches, such as chemo- and radiation therapy, result in poor survival rates and high tumour recurrence rates, which are the most common issues that need to be improved upon. The aim of this study was to evaluate the therapeutic properties of 45S5 bioactive glass (BG) for targeting bone tumours. The viability of the cells derived from osteosarcoma, chondrosarcoma, and giant cell tumours was significantly reduced in the presence of 45S5-BG. In contrast, the viability of non-malignant osteoblast-like cells, chondrocytes, and bone marrow-derived stromal cells was not or only slightly affected. While alterations to the particle surface induced by heat treatment, acid etching, or incubation in a simulated body fluid had only minor effects on cytotoxicity, reducing the particle size or sintering the material significantly improved the cytotoxic effect of 45S5-BG. Further, using a chicken chorioallantoic membrane assay, the co-transplantation of 45S5-BG resulted in a significant reduction in tumour formation in vivo. Given the known positive effects of BGs on bone regeneration, our findings suggest that 45S5-BG holds great potential for the development of new and effective bone tumour therapies, with minimal side effects on non-malignant cells and simultaneous contribution to bone healing.